The Effects of Transient Temperature around Welds on Mechanical Properties of A36 Steel Plate - Jufri, Mohammad (Journal of Energy, Mechanical, Material and Manufacturing Engineering, 2016)
There are various ways for welding experts to improve their production quality, and one of which is by designing a particular type of welding tool. Besides aiming to replace the function of operatorâs body parts, the tool is also able to control buckling distortions, crack propagations, and stress voltage, as well as to save an additional work, which is the heat treatment after welding process. The best method to control buckling distortions from the thin plate is by applying pre-heating and thermal tensioning. Thermal tensioning is the characterization by heat application during welding process. Transient thermal tensioning is a supporting tool around the weld which is given periodical heat by following the movement of arc welding. The purpose of this research was to minimize distortions and maximize the performance (mechanical properties) of welding joints shaped due to the transient temperature application during the welding process. The method employed in this research was experiment by using A36 steel plate with transient temperature variation of 100, 200, and 300oC, with velocity of 8 mm/s and heater (toutch) distance of 4, 6, and 8 cm. In this research, the researcher conducted tensile-strength test according to the JIS G 3101 standard and hardness test around weld, HAZ (Heat Affected Zone), and parent metal.The findings showed that the change of transient temperature and heater distance affected the mechanical properties (hardness and tensile strength) of A36 steel. The highest level of hardness was obtained in the temperature of 200Â°C and heater distance of 6 cm, which was as much as 404 VHN. The highest level of tensile strength was obtained in the temperature of 200Â°C and heater distance variation of 8 cm with yield stress of 302 Mpa and maximum tensile strength of as much as 491 Mpa.